A bright future (Volume 6) - Birol, Faith (European Investment Bank, 2019)
There is good news and bad news in the renewable energy industry. We have made a lot of progress in green energy over the past few years as technologies have improved and the costs of production have fallen. But we are not doing enough. Fatih Birol, Director of the International Energy Agency, writes that despite progress, renewables still have a long way to go. We need much more action to make sure that everyone has access to energy and that we slow climate change, reduce pollution and make the world sustainable. This is the sixth essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people's lives around the globe.